To model bolted parts for tolerance analysis using variational model - Polini, Wilma; Marziale, Massimiliano (International Journal of Engineering and Technology, 2015)
Mechanical products are usually made by assembling many parts. Among the different type of links, bolts are widely used to join the components of an assembly. In a bolting a clearance exists among the bolt and the holes of the parts to join. This clearance has to be modeled in order to define the possible movements agreed to the joined parts. The model of the clearance takes part to the global model that builds the stack-up functions by accumulating the tolerances applied to the assembly components. Then, the stack-up functions are solved to evaluate the influence of the tolerances assigned to the assembly components on the functional requirements of the assembly product.The aim of this work is to model the joining between two parts by a planar contact surface and two bolts inside the model that builds and solves the stack-up functions of the tolerance analysis. It adopts the variational solid model. The proposed model uses the simplified hypothesis that each surface maintains its nominal shape, i.e. the effects of the form errors are neglected. The proposed model has been applied to a case study where the holes have dimensional and positional tolerances in order to demonstrate its effectiveness.